2017
DOI: 10.1186/s40360-017-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven prediction of adverse drug reactions induced by drug-drug interactions

Abstract: BackgroundThe expanded use of multiple drugs has increased the occurrence of adverse drug reactions (ADRs) induced by drug-drug interactions (DDIs). However, such reactions are typically not observed in clinical drug-development studies because most of them focus on single-drug therapies. ADR reporting systems collect information on adverse health effects caused by both single drugs and DDIs. A major challenge is to unambiguously identify the effects caused by DDIs and to attribute them to specific drug intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Older studies implicate ADRs to be one of the top 10 causes of fatality in the US (Lazarou et al, 1998) , while more recent studies report that they account for anywhere for 2.7% to 15% of hospitalizations (Liu et al, 2017;Miguel et al, 2012) . Drug-drug interactions account for upto 30% of ADRs (Iyer et al, 2014) , and are known to affect clinical outcomes in 80% of those observed in cancer patients (Beijnen & Schellens, 2004) .…”
Section: Prevalence and Salient Statisticsmentioning
confidence: 99%
“…Older studies implicate ADRs to be one of the top 10 causes of fatality in the US (Lazarou et al, 1998) , while more recent studies report that they account for anywhere for 2.7% to 15% of hospitalizations (Liu et al, 2017;Miguel et al, 2012) . Drug-drug interactions account for upto 30% of ADRs (Iyer et al, 2014) , and are known to affect clinical outcomes in 80% of those observed in cancer patients (Beijnen & Schellens, 2004) .…”
Section: Prevalence and Salient Statisticsmentioning
confidence: 99%
“…Instead of employing drug structures in DDI prediction, Ferdousi et al constructed a method based on drug functional similarities consisting of carriers, transporters, enzymes and targets . Ruifeng et al built large‐scale drug‐protein interaction profiles with protein‐chemical linked data from the STITCH database to construct the prediction models for drug pairs that are likely to induce adverse drug reactions via synergistic DDI, and then evaluated the performance using the TWOSIDES database …”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…12 Ruifeng et al built large-scale drug-protein interaction profiles with protein-chemical linked data from the STITCH database to construct the prediction models for drug pairs that are likely to induce adverse drug reactions via synergistic DDI, and then evaluated the performance using the TWOSIDES database. 13 Specifically, Vilar et al used the molecular structure similarity, 14 IPF similarity, 15 3D pharmacophoric similarity, 16 drug-target similarity and adverse drug effect similarity to construct a new protocol and the STATISTICA software for predicting DDI with 84% accuracy. 17 Cheng et al developed similarity-based machine learning support vector machine (SVM) models using phenotypic, therapeutic, chemical structure and genomic features for predicting DDI at the performance level of AUROC = 0.67.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%
“…Data-driven healthcare research has been proposed to achieve this goal [28][29]. In recent decades, various types of data-driven healthcare researches have been proposed, for instance, Genome-Wide Association Study (GWAS) [30][31] and Phenome-Wide Association Study (PheWAS) [32][33] have been developed to find associations between genes, diseases and drugs; drug-drug interaction studies have been implemented to detect adverse drug interactions [34]; predictive models are used to predict diseases such as Alzheimer [35] and suicide [36] at an earlier time; computational algorithms and statistical models are leveraged to identify risk factors related to patient outcomes such as unplanned readmission rates [38], mortality rates [39] and prolonged length of stay [40][41];…”
Section: Introductionmentioning
confidence: 99%